Modernism and the social sciences : Anglo-American exchanges, c.1918-1980 - Bevir, Mark (Cambridge University Press, 2017)
This wide-ranging and original study reveals how prevalent modernism has become in the social sciences. With contributions from a number of leading international scholars, Modernism and the Social Sciences explores the rise and nature of modernist tropes and approaches within social sciences such as economics, econometrics, behaviourism, sociology, administrative science, linguistics, history and anthropology. The essays demonstrate how the social sciences turned away from the developmental historicisms of the nineteenth century. Instead, social scientists have become increasingly committed to synchronic and formal explanations that rely on models, correlations and ideal types, and they have increasingly appealed to systems and functions and to institutions and norms. This book will reveal wider trends and parallels to specialists in particular disciplines and it will also appeal to those interested in intellectual history and social science theory. This volume is a companion to Historicism and the Human Sciences in Britain, a product of the Mellon project on Britain's Modernity, published by Cambridge in 2017.